The social economic development index: a new measurement of development - Tha’r Mutlaq Mohammed Ayasrah (Penerbit Universiti Kebangsaan Malaysia, 2012)
The human development index (HDI) is published annually by the United Nations Development Program and has played an influential role in the debate on human development for many years. However, it has been widely argued for several reasons that the HDI contains several weaknesses and is an inappropriate mechanism by which to measure human development. Additionally, the HDI does not take into account further important indicators, such as unemployment, poverty and environment, alongside GDP per capita; expected years of schooling and mean years of schooling; and life expectancy at birth. No index is perfect and the HDI of the UNDP reflects this fact. The present study proposes the social economic development index (SEDI) as a new means to measure the development level of countries. The SEDI uses more indicators than the three presently examined in the HDI. The study also suggests applying the development status matrix (DSM), which assists in classifying countries into groups according to development status, specifically focusing on the dynamic characteristics of underdeveloped countries. In conclusion, this study clearly demonstrates the importance of utilizing the SEDI and the DSM to measure a country’s development.